Prospek Kerjasama Bilateral Indonesia-Malaysia bagi Kesejahteraan Masyarakat di Wilayah Perbatasan - Yovinus Yovinus (Dinamika Global : Jurnal Ilmu Hubungan Internasional, 2016)
Opportunities and challenges in today’s era of globalization also affect the relationship between Indonesia and Malaysia. As the two allied countries which have a sea and land borders, there are many issues that arise as a result of interaction between citizens of both countries and the issue of political and teritorial issues which sometimes led to tensions between the two countries. In spite of it all there is another problem that is actually more substansial and that is people welfare. Commonly the border region can be regarded as disadvantaged areas, and most of its inhabitants live in poverty. This indicated the failure of both governments take advantage of the potential of natural resources and human resources as well as the geographical conditions that actually have great potential to inprove the well-being of border residents. However, with a good cooperation and mutual benefit in the future pattern of the pattern of bilateral cooperation has a great opportunity in order to improve the welfare of society.